AB0576 Evaluation of surfactant protein-D and KL-6 as potential pulmonary safety biomarkers during mavrilimumab treatment. (23rd January 2014) - Spitz, S.; Wilkins, D.; Esfandiari, E.; Godwood, A.; Roskos, L.; Ryan, P.; Magrini, F.
Abstract : Background: Mavrilimumab is a high-affinity, fully human immunoglobulin G (IgG) monoclonal antibody that selectively binds to the α subunit of GM-CSF receptor (GM-CSFRα) and is being evaluated for the treatment of rheumatoid arthritis. GM-CSF signaling is critical to regulate the clearance of surfactant lipids and proteins by the pulmonary alveolar macrophages. In both autoimmune and hereditary PAP, loss of GM-CSF signaling blocks the terminal differentiation of alveolar macrophages in the lungs impairing the ability of alveolar macrophages to catabolize surfactant and perform many host defense functions. The inhibition of GM-CSF by mavrilimumab might affect the regulation of lung homeostasis of pulmonary surfactant by alveolar macrophages (Trapnell and Whitsett, 2002). Surfactant Protein-D (SP-D) is a member of the collagenous subfamily of glycoproteins and calcium-dependent lectins. In the lungs, SP-D participates in the innate response to inhaled microorganisms and organic antigens through host defense functions and may be related to a number of human pulmonary diseases. Krebs von den Lungen-6 (KL-6) is a member of the collagenous subfamily of glycoproteins secreted by type II pneumocytes and has emerged as a potential surrogate biomarker of alveolitis. These two markers may identify changes associated with accumulation of surfactant in alveoli that may be the result of interruption of GM-CSF signaling. Objectives: SP-D and KL-6 were monitored in serum as potential pulmonary safety biomarkers for mavrilimumab in clinical study EARTH, "A Phase 2 Randomized, Double-blind, Placebo-controlled, Multiple Ascending Dose Study to Evaluate the Efficacy and Safety, of CAM-3001 in Subjects with rhE umatoid ARTH ritis. Methods: Levels of SP-D and KL-6 were measured during the 12 week treatment and safety follow-up phase of the study on 182 subjects. Commercially available ELISAs were qualified as a fit-for-purpose method and utilized to analyze serum samples collected at baseline and on Days 29, 85 and 169. Results: The results of these analyses showed no changes in serum levels of SP-D and KL-6 in the mavrilimumab-treated subjects and no dose-dependent effects on the concentration of SP-D and KL-6. The results of analysis of the two potential biomarkers are consistent with the safety profile observed for the study. Pulmonary-related adverse events (AEs) reported in the study were generally mild or moderate in intensity; the most common events included decrease in carbon monoxide diffusing capacity (placebo 4 [5.1%]; mavrilimumab 19 [11.9%]), nasopharyngitis (placebo 2 [2.5%]; mavrilimumab 10 [6.3%]) and upper respiratory tract infections (placebo 4 [5.1%]; mavrilimumab 6 [3.8%]). No clinical significant lung problem was detected for DLCO deterioration cases assessed by the pulmonologists. Conclusions: These findings indicate that no changes in serum levels of two potential pulmonary safety biomarkers, SP-D and KL-6, that have been reported to be associated with pulmonary diseases, could be detected over the 12 week treatment period with mavrilimumab in the Phase 2 clinical study EARTH. References: Trapnell BC, Whitsett JA. GM-CSF regulates pulmonary surfactant homeostasis and alveolar macrophage-mediated innate host defense. Annu Rev Physiol. 2002;64:775-802. Disclosure of Interest: None Declared